Secessionists and Other Scoundrels : Selections from Parson Brownlow's Book - Brownlow, William Gannaway, 1805-1877 (Book collections on Project MUSE., 1999)
"East Tennessee newspaper editor and Methodist preacher William G. "Parson" Brownlow, a man of fervent principles and combative temperament, gained fame during the secession crisis as a staunch, outspoken southern unionist. Unlike most southern unionists, however, Brownlow refused to renounce his loyalty to the Union after the Civil War broke out. He continued to write editorial tirades against the Confederacy until forcibly silenced by southern authorities. Arrested, jailed, and ultimately banished to the North, Brownlow continued his war of words against the Confederacy through speaking tours and through the publication in 1862 of Sketches of the Rise, Progress, and Decline of Secession; with a Narrative of Personal Adventures Among the Rebels - a bestselling but ill-organized hodgepodge of his editorials, speeches, letters, and commentary. This book, a collection of selected excerpts from Brownlow's original, offers an accessible and powerful explication of the parson's Unionism and a moving narrative of his travails under Confederate rule, without sacrificing the vitriolic prose and scathing wit for which he was celebrated and denounced."--adapted from jacket.